A new approach to religious orientation : the commitment-reflectivity circumplex - Krauss, Stephen W.; Hood, Ralph W., Jr., 1942- (Amsterdam : Editions Rodopi, 2013)
The Commitment-Reflectivity Circumplex (CRC) model of religious orientation is introduced and the results from a series of model testing experiments are reviewed. The CRC model was developed through a series of studies in the United States and Romania and was created in an effort to reduce the theoretical and empirical difficulties associated with the traditional Allportian religious orientation models and measures. Toward this end, the difficulties associated with the Allportian religious orientation models are reviewed, along with how the CRC model attempts to address them. Next, the CRC model is introduced and a list of its predictions are given and compared to those of the Allportian models. The results of 10 model testing studies using multidimensional scaling are then reviewed. In these studies, the CRC model, which posits that all religious orientation can be located along dimensions of commitment (importance) and reflectivity (complexity), is found to be more accurate than the Allportian models in both the U.S. and Romania. Based on these studies, the meaning and interpretation of the Allportian measures are reviewed and new interpretations are suggested. Lastly, the relationships between religious orientation, mental health, personality, ideology, and prejudice are explored. In every area, the CRC model, and the measures based on it, show superior predictive abilities to traditional approaches in both the United States and Romania.
Definitions -- Religious orientation -- The search for new religious orientations and the development of the CROI -- Model testing -- Traditional approaches to religious orientation -- Religious orientation and prejudice -- Religious orientation, mental health, personality traits and ideology.
Print version record.
Includes bibliographical references (pages 221-231).
Master record variable field(s) change: 072
Keywords: Religion; Psychology and religion; Religion and sociology; Social sciences -- Methodology; Personality; RELIGION -- Comparative Religion; RELIGION -- Essays; RELIGION -- Reference; Personality; Psychology and religion; Religion; Religion and sociology; Social sciences -- Methodology; Electronic books